Determination of Sulfasalazine in Sulfasalazine Tablets Using Silver Nanoparticles: Sulfasalazine using silver nanoparticles - Zahra Ramezani; Najmeh Dibaee (Iranian Journal of Pharmaceutical Sciences, 2012)
Resonance light scattering (RLS) intensity of silver nanoparticles in the presence of sodium dodecylsulphate was quenched on addition of sulfasalzine. The quenching extent was shown to be proportional to the sulfasalazine concentration. Effect of different parameters such as pH, volume and kind of buffer, silver nanoparticles concentration, sodium dodecylsulphate (SDS) concentration, and waiting time on RLS quenching were investigated. Calibration curve was linear in the range of 10 to 70 μg ml-1. Detection limit was determined as 0.012 mg.ml-1. The method was successfully applied to the determination of sulfasalazine in different batch numbers of sulfasalazine tablets. The results were compared with those determined by USP method. Reasonable agreements were observed.